2013
DOI: 10.1097/sle.0b013e3182747af7
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy Versus Open Distal Gastrectomy for Advanced Gastric Cancer

Abstract: The oncologic outcomes of LADG for AGC patients were comparable with open approach. Although open distal gastrectomy may be associated with shorter operative time, patients undergoing laparoscopic approach may be benefitted from a shorter hospital stay and a faster resumption without translation into an increase in both postoperative morbidity and mortality. Nevertheless, further prospective, controlled studies, and extended follow-up are needed for a more comprehensive comparison between the 2 procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 20 publications
2
28
0
Order By: Relevance
“…The clinical significance of a composite meta-analysis of RCTs and CCSs remains unclear, although various meta-analyses of both RCTs and CCSs have been published recently [7,8,39]. The value of meta-analyses of CCSs remains controversial, because CCSs often include groups of patients mismatched for background characteristics.…”
Section: D2mentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical significance of a composite meta-analysis of RCTs and CCSs remains unclear, although various meta-analyses of both RCTs and CCSs have been published recently [7,8,39]. The value of meta-analyses of CCSs remains controversial, because CCSs often include groups of patients mismatched for background characteristics.…”
Section: D2mentioning
confidence: 99%
“…In fact, in a meta-analysis reported by Viñuela et al, "handassisted," "pylorus-preserving," "robotically-assisted," and "gasless" LDG were included in the general LDG group [8]. In another meta-analysis of advanced gastric cancer by Qiu et al, some of the selected studies included patients who underwent D1 lymphadenectomy, which is considered an insufficient treatment [39]. Our meta-analysis also had limitations despite the inclusion of studies in which cases were matched as closely as possible.…”
Section: D2mentioning
confidence: 99%
“…There were no significant differences between the two groups in number of LN dissections, postoperative mortality, overall complications, and 3- year overall survival rate. Therefore, the authors concluded that the oncologic outcomes of LADG for AGC patients were comparable with an open approach [45]. …”
Section: Laparoscopic Gastrectomy For Advanced Cancermentioning
confidence: 99%
“…With the development of laparoscopic instruments and the accumulation of surgical technique, laparoscopyassisted gastrectomy occupies an important position in field of surgical treatment for gastric cancer (Zhao et al, 2013;Qiu et al, 2013;Jiang et al, 2013). Several advantages of this approach have been reported by different centers.…”
Section: Discussionmentioning
confidence: 99%